Peran Ukuran Perusahaan Sebagai Moderasi Rasio Keuangan Terhadap Harga Saham - Franciska Katarina Pattynama (Owner : Riset dan Jurnal Akuntansi, 2025)
Several previous studies have shown different results regarding the importance of using financial information. This research aims to determine the effect of financial ratios consisting of CR (Current Ratio), DAR (Debt to Asset), TAT (Total Asset Turnover), ROE (Return of Equity) and ROA (Return of Assets) on Company Share Prices. Apart from that, this research aims to determine the moderating role of company size in strengthening the influence of financial ratios on company share prices. This research uses quantitative data with a purposive sampling approach on companies indexed LQ45 on the Indonesia Stock Exchange in 2018-2020. This research uses multiple linear regression analysis to test HI and the moderated regression analysis method to test H2. The purpose of moderating regression analysis is to find out whether the moderating variable will strengthen or weaken the relationship between the independent variable and the dependent variable. The moderating variable in this research is included in the Quasi Moderator Variable. The research results show that hypothesis 1 is accepted that the ROE (Return on Equity), ROA (Return on Assets), Debt to Assets Ratio (DAR) ratio has an effect on stock prices. Meanwhile, Total Asset Turnover has no influence on share prices. Hypothesis Moderation Test Results 2 The company size variable strengthens the influence of Current Ratio, ROE (Return on Equity), ROA (Return on Assets), and Total Asset Turnover (TAT) on stock prices, but on the Debt to Assets Ratio (DAR) company size does not strengthen the influence of DAR on share prices.